The positive effects of explaining the underlying mechanisms (how it works) when promoting healthy behaviors. Issue 1 (2nd January 2020) - Pettinico, George; Debevec, Kathleen
Abstract: Health-care providers, governments, and countless organizations struggle, often unsuccessfully, to convince the public to adhere to healthier and safer lifestyles. Through three experiments, our research suggests communicating information on how —providing details of the processes by which healthy/safer behaviors actually work to bring about personal benefits—has a significant and positive impact on the persuasiveness of the message compared to communicating benefits alone. The downside of the addition of this how information is that these messages may be seen as more burdensome to digest. The authority of the messenger did not have an impact on this effect.